Radiobiological Modeling Based on (18)F-Fluorodeoxyglucose Positron Emission Tomography Data for Esophageal Cancer - Guerrero, Mariana (J Nucl Med Radiat Ther, 2014)
BACKGROUND: We investigated the relationship of standardized uptake values (SUVs) to radiobiological parameters, such a 25 s tumor control probability (TCP), to allow for quantitative prediction of tumor response based on SUVs from (18)F fluorodeoxyglucose ((18)F-FDG) positron emission tomography (PET) before and after treatment for esophageal cancer. METHODS: We analyzed data from 20 esophageal cancer patients treated with chemoradiotherapy (CRT) followed by surgery. Tumor pathologic response to CRT was assessed in surgical specimens. Patients underwent (18)F-FDG PET imaging before and after CRT. Rigid image registration was performed between both images. Because TCP in a heterogeneous tumor is a function of average cell survival, we modeled TCP as a function of <SUV(R)>, a possible surrogate for average cell survival (<SUV(R)>=<SUV(after)/SUV(before)>). TCP was represented by a sigmoid function with two parameters: SUV(R50), the <SUV(R)> at which TCP=0.5, and γ(50), the slope of the curve at SUV(R50). The two parameters and their confidence intervals (CIs) were estimated using the maximum-likelihood method. The correlation between SUV before CRT and SUV change <SUV(before) – SUV(after)> was also studied. RESULTS: A TCP model as a function of SUV before and after treatment was developed for esophageal cancer patients. The maximum-likelihood estimate of SUV(R50) was 0.47 (90% CI, 0.30-0.61) and for γ(50) was 1.62 (90% CI, 0-4.2). High initial SUV and larger metabolic response (larger <SUV(before) –SUV(after)>) were correlated, and this correlation was stronger among responders. CONCLUSIONS: Our TCP model indicates that <SUV(after)/SUV(before)> is a possible surrogate for cell survival in esophageal cancer patients. Although CIs are large as a result of the small patient sample, parameters for a TCP curve can be derived and an individualized TCP can be calculated for future patients. Initial SUV does not predict response, whereas a correlation is found between surrogates for initial tumor burden and cell kill during therapy.